Understanding Focusing-Oriented Psychotherapy - Boukydis, Zack; Kántor, Árpád (Psychological Counseling and Psychotherapy, 1970)
This paper outlines the fundamental understanding of Focusing-Oriented Psychotherapy. Eugene Gendlin was the first to articulate the theory of experiencing, and the integration of focusing into psychotherapeutic practice. The basic methods of focusing-oriented psychotherapy are described and put into the interpersonal context of therapy. The paper includes a resource section so that the reader can read more about the theory, application and recent development of focusing-oriented psychotherapy.